Masculinised (American) Eyes, Feminised (Malaysian) Dreams? A Psychoanalytic Study of Robert Raymer's Collection of Short Stories in Lovers and Strangers Revisited. - Aziz, Jamaluddin (2006)
Pennsylvania-born Robert Raymer moved to Malaysia more than 20 years ago (1985) and since then has written several stories by using Malaysia, especially Penang, as their major setting. Married to two Malaysians - not simultaneously (his ex-wife was a Malay and his present is a Sarawakian - from East Malaysia).